Credit market imperfection, lack of entrepreneurs and capital outflow from a developing economy - Marjit, Sugata,Mishra, Suryaprakash (CESifo, Center for Economic Studies & Ifo Institute, 2020)
This paper explores the impact of credit market on the entrepreneurs and demand for credit in a credit constrained economy and the resultant impact on the capital flows. In standard trade models the capital flows across countries are explained as a result of the rate of return differentials due to presence/absence of capital among the countries whereby capital flows from the capital rich countries to capital poor countries. We show that the rate of return differentials could arise due to presence/absence of entrepreneurs, i.e., low price of capital in autarky may reflect lack of demand for credit due to scarcity of entrepreneurs and not capital abundance and eventually may lead to capital outflow from a capital scarce country. This is a different way of echoing the sentiment of the well-known
10419/223587
Keywords: Graue Literatur; credit market imperfection; credit rationing; redistribution; entrepreneurs; capitalflows